Bilious vomiting in Tracheo-oesophageal fistula with oesophageal atresia, Situs Inversus incompletus and gastro-biliary fistula. A diagnostic conundrum - Oluwaseun A. Ladipo-Ajayi, MBChB, FWACS; Olukayode O. Olayade; Adesoji Ademuyiwa; Uzoma Ifezue; Kasiemobi Uchime (Elsevier, 2020)
The diagnosis of oesophageal atresia with or without fistula has traditionally been premised on the clinical finding of excessive salivation, regurgitation of feeds with attendant respiratory compromise in affected neonates. In addition, inability to pass an appropriate sized oesophageal tube into the stomach is confirmatory. OA/TOF is documented to be associated with other congenital abnormalities in up to 50% of cases. These often affect the outcome of treatment. A presentation of OA/TOF with bilious vomiting is rare and requires a high index of suspicion and appropriately selected investigations to cinch the diagnosis. Thus bilious vomiting in a neonate does not rule out the diagnosis of OA/TOF and it is important to ensure a thorough examination and investigation in every surgical neonate. Keywords: Situs inversus, Tracheo-oesophageal fistula, Bilious vomiting, Gastrobiliary fistula